Effects of Carbon Chain Length of Acrylate Monomer on Sizing Properties of Locust Bean Gum-g-P (AA-co-Acrylate). Issue 4 (July 2022) - Lu, Haojie; Ji, Zhihao; Li, Manli; Jin, Enqi; Zhou, Jiu
In order to impart good application properties to locust bean gum size for all-polyester yarn, a series of acrylate monomers including methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and common hydrophilic monomer–acrylic acid were grafted onto molecular chains of native locust bean gum to obtain locust bean gum- g -P(AA-co-acrylate) products with similar grafting ratios through Fenton's reagent, respectively. The effects of carbon chain length of the series of acrylates on sizing properties of the grafted locust bean gum for polyester warp were studied. It was found that by grafting acrylates onto the molecular chains of locust bean gum the sizing properties of the locust bean gum were improved markedly. Under the condition of similar grafting ratios, locust bean gum- g -poly(AA-co-methyl acrylate) showed the highest apparent viscosity, water solubility, film strength, wettability, and adhesion to polyester fiber in all the grafted locust bean gum prepared. Meanwhile, locust bean gum- g -poly(AA-co-butyl acrylate) and locust bean gum- g -poly(AA-co-2-ethylhexyl acrylate) had the highest wear resistance and elongation of sizing film, respectively. The modified locust bean gum grafted with acrylate monomers with different carbon chain lengths was able to meet various requirements in the sizing process for polyester yarn.